Frontiers of difference: control as governance, precarity, and agencies in the journeys of LGBTQI+ migrants at the borders of Brazil and Mexico - Williamson Modesto, Macarena Francisca (Frontiers in Human Dynamics, 2026)
This original research analyses continuities and ruptures in the trajectories of LGBTQI+ migrants, focusing on lesbians and transgender experiences at Brazilian and the Mexican borders regions as empirical contexts. Although these trajectories vary in terms of time, geopolitical scenarios and the ways in which social markers of difference shift through border crossings, these displacements suggest, as a transversal characteristic, that the production of uncertainty is a form of governance of human mobility. These displacements suggest that the global migration control regime is framed by a heteronormative and familistic order that shapes gender hierarchies and inequalities in the transit of LGBTQI+ migrants across Latin American borders. The underlying argument is that all migration policies are gender policies. In the cases discussed here, the productive relations between gender, sexuality and migration are based on cis-heterocentric gender norm that is structurally rooted in a limited binary gender system. This system becomes insufficient when confronted with the experiences of lesbian and trans migrants in transit across borders of the Global South. These displacements in the Brazilian and the Mexican borders shed light on the inconsistencies and ambiguities that gender dimorphism brings to humanitarian policies for LGBTQI+ migrants. Finally, the results section explores the resistance and survival strategies employed by LGBTQI+ migrants in response to the precarious and uncertain conditions they face when crossing borders of Latin America.